Thirst and drinking in North American watersnakes (Nerodia spp.) - Edwards, Matthew (J Exp Biol, 2021)
We quantified drinking behavior in three species of North American watersnakes: Nerodia clarkii, which is a marine or brackish water amphibious species, and Nerodia fasciata and Nerodia taxispilota, both freshwater amphibious species. All three species have relatively small and similar thresholds of dehydration (TH, approximately −4% loss of body mass) that elicit thirst and drinking of fresh water. These species have higher thirst sensitivity than several species of hydrophiine and laticaudine sea snakes, which are characterized by much lower TH (greater dehydration, −9% to <−20%). Nerodia clarkii, which is often found in coastal oceanic water, refused to drink seawater, but drank fresh water when dehydrated. In separate trials involving dehydration of N. clarkii and N. fasciata that were concurrently fed fish at regular intervals, snakes eventually refused to eat at TH of approximately −12% of original body mass, but resumed eating after they were allowed to drink fresh water and rehydrate. The drinking behaviors of Nerodia corroborate previous data on the importance of fresh water for drinking, and they complement growing evidence that dietary water does not itself mitigate dehydration in snakes. These new data increase understanding of water relationships in the context of evolutionary transitions from land to sea, and they emphasize the importance of fresh water resources in the conservation of coastal and marine species of reptiles.